DIDACTIC PLAY AS ONE OF EFFECTIVE FORMS OF LEARNING IN HISTORY LESSONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the advantages of using didactic games in the lesson and the methodology for using them.